Dyspraxia and Agnosia in Schizophrenia - P. F. Liddle; S. Haque; D. L. Morris; T. R. E. Barnes (Behavioural Neurology, 1993)
A battery of tests for dyspraxia and agnosia was administered to 51 chronic schizophrenic patients to test the hypothesis that these cortical neurological signs are associated with psychomotor poverty syndrome (poverty of speech, flat affect, decreased spontaneous movement), disorganization syndrome (various disorders of the form of thought, inappropriate affect), abnormal involuntary movements, cognitive impairment, and duration of illness. The findings supported all elements of the hypothesis, and in particular, demonstrated a strong correlation of cortical signs with psychomotor poverty and with cognitive impairment.